2020
DOI: 10.3892/etm.2020.9404
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of neurointervention combined with intravenous thrombolysis in the treatment of ischemic cerebrovascular disease and its influence on neurological function and prognosis of patients

Abstract: The present study aimed to investigate the efficacy of neurointervention combined with intravenous thrombolysis in the treatment of ischemic cerebrovascular disease (ICD) and its influence on the neurological function and prognosis of patients. A total of 119 patients with ICD admitted to Xinxiang Central Hospital (Xinxiang, China) from May 2013 to September 2015 were selected. Among them, 65 patients were enrolled in the control group and treated with intravenous thrombolysis, whereas the other 54 patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(17 reference statements)
1
1
0
Order By: Relevance
“…This study compared the short-term therapeutic efficacy, cerebral hemodynamics, VEF, and OS indexes of ICVD patients treated with conventional IVT and those with DSA-guided neurointerventional thrombolysis. The results showed a significantly higher ORR in patients receiving DSA combined with neurointerventional thrombolysis compared those with conventional IVT alone, similar to the research of Li et al [33]. Besides, we found decreased NIHSS scores in both cohorts after treatment, especially in OG.…”
Section: Discussionsupporting
confidence: 90%
“…This study compared the short-term therapeutic efficacy, cerebral hemodynamics, VEF, and OS indexes of ICVD patients treated with conventional IVT and those with DSA-guided neurointerventional thrombolysis. The results showed a significantly higher ORR in patients receiving DSA combined with neurointerventional thrombolysis compared those with conventional IVT alone, similar to the research of Li et al [33]. Besides, we found decreased NIHSS scores in both cohorts after treatment, especially in OG.…”
Section: Discussionsupporting
confidence: 90%
“…These results indicated that VCI can damage multiple sets of cognitive-related fibers and affect fiber conduction function. Li et al [ 19 ] also illustrated this point in the study on the influence of cerebrovascular diseases on neurological function. Therefore, as the severity of the disease progresses in VCI patients, the white matter fibrosis becomes more severe and the level of neurological function decreases.…”
Section: Discussionmentioning
confidence: 90%